2021
DOI: 10.31234/osf.io/dg5mw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal response modelling uncovers electrophysiological correlates of trial-by-trial error-driven learning

Abstract: Humans learn from statistical regularities in the environment. We tested if prediction and prediction error may play a role in such learning in the brain. We used Error-Driven Learning (EDL) to simulate participants’ trial-by-trial learning during exposure to a bimodal distribution of non-native lexical tones. We simulated incremental trial-by-trial learning to get estimates of the degree of expectation of upcoming stimuli over the course of the experiment. The expectation estimates were combined with Temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…While previous work has shown the predictive power of errordriven learning by means of the Rescorla-Wagner rule in many areas of language research (e.g. Ramscar et al, 2013;Nixon and Tomaschek, 2021;Ellis, 2006a,b) as well as trial-to-trial learning (Chuang and Baayen, 2021;Lentz et al, 2021;Tomaschek et al, 2022), the present work extends these findings by showing that error-driven learning implemented with the Widrow-Hoff learning rule can also capture trial-to-trial learning effects in a much richer and more realistic model of lexical processing incorporating state-of-the-art representations of semantics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous work has shown the predictive power of errordriven learning by means of the Rescorla-Wagner rule in many areas of language research (e.g. Ramscar et al, 2013;Nixon and Tomaschek, 2021;Ellis, 2006a,b) as well as trial-to-trial learning (Chuang and Baayen, 2021;Lentz et al, 2021;Tomaschek et al, 2022), the present work extends these findings by showing that error-driven learning implemented with the Widrow-Hoff learning rule can also capture trial-to-trial learning effects in a much richer and more realistic model of lexical processing incorporating state-of-the-art representations of semantics.…”
Section: Discussionmentioning
confidence: 99%
“…They have generally been designed for modelling specific purposes, and are often limited to a few items (e.g. Oppenheim et al, 2010;Lentz et al, 2021;Ramscar et al, 2013;Tomaschek et al, 2022). Models such as ACT-R (Anderson and Lebiere, 1998) model the learning and forgetting of stimuli also during experiments, but they treat words as units and model forgetting as a function of time (Van Rijn and Anderson, 2003), without taking into account interference caused by the learning of intervening stimuli, which is a crucial characteristic of the Rescorla-Wagner rule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In first language acquisition, Tomaschek (2020, 2021) present a computational model of early infants' learning of speech by using the incoming acoustic signal to predict upcoming acoustic signal. Apart from phonetic learning, error-driven learning has also been found to play a role in word learning (Ramscar et al, 2013a(Ramscar et al, , 2010(Ramscar et al, , 2011, morphological learning (Ramscar and Yarlett, 2007;Ramscar et al, 2013b;Tomaschek et al, 2019;Hoppe et al, 2020) and speech production (Tucker et al, 2019;Tomaschek and Ramscar, 2022) and speech perception (Shafaei-Bajestan and .There is also evidence for trial-by-trial error-driven learning in the brain (Lentz et al, 2022) and during lexical decision (? ).…”
Section: Learning Mechanismsmentioning
confidence: 99%
“…The Rescorla-Wagner model was developed to capture the observation that rather than contiguity, learning was instead driven by surprise / prediction error and uncertainty (Kamin, 1969a;Rescorla, 1988), hence the term 'error-driven learning'. The Rescorla-Wagner model has proven remarkably successful in predicting human category learning (Gluck & Bower, 1988) and has recently been proposed as an account of human language acquisition (Ramscar & Yarlett, 2007;Ramscar, Yarlett, Dye, Denny, & Thorpe, 2010;Ramscar, Dye, & McCauley, 2013), predicting many linguistic phenomena (Baayen, Shaoul, Willits, & Ramscar, 2016;Baayen, Milin, Durdević, Hendrix, & Marelli, 2011;Ellis, 2006;Lentz, Nixon, & van Rij, 2022;Nixon, 2020;Nixon & Tomaschek, 2020, 2021. In a study investigating the learning mechanisms underlying second language speech sound acquisition, Nixon (2020) demonstrated that a number of key principles of error-driven learning also apply to human learning of speech, including Kamin's 'blocking effect' (Kamin, 1968(Kamin, , 1969b, cue competition, prediction and unlearning (Ramscar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%